АНАЛИЗ СТАТЕЙ ПО ЭРОЗИИ ПОЧВ В ЦЕНТРАЛЬНОЙ АЗИИ, ОПУБЛИКОВАННЫХ В БАЗЕ ДАННЫХ SCOPUS В ПЕРИОД 1993-2022 ГГ (Scientific journal of the Fergana State University, 2024)
Soil is a porous and biologically active medium located in the upper part of the earth's crust. It is a valuable resource for food production and it demands a long time to recover. Soil erosion is one of the most important issues for countries based on agriculture. For this review article, 126 articles published in English in the Scopus database on the topic of soil erosion in Central Asian countries between 1993 and 2022 were analyzed. The results showed that a higher number of publications belonged to Uzbekistan over the whole period but the funding index was more dominant in Kazakhstan. During the considered period, the number of publications on soil erosion has gratifyingly increased in the last years compared to the first years, which indicates that the attention to the topic has increased in recent years.